Safety, tolerability, pharmacokinetics, and immunogenicity of a human monoclonal antibody targeting the G glycoprotein of henipaviruses in healthy adults: a first-in-human, randomised, controlled, phase 1 study. Issue 4 (April 2020) - Playford, Elliott Geoffrey; Munro, Trent; Mahler, Stephen M; Elliott, Suzanne; Gerometta, Michael; Hoger, Kym L; Jones, Martina L; Griffin, Paul; Lynch, Kathleen D; Carroll, Heidi; El Saadi, Debra; Gilmour, Margaret E; et al.
Summary: Background: The monoclonal antibody m102.4 is a potent, fully human antibody that neutralises Hendra and Nipah viruses in vitro and in vivo. We aimed to investigate the safety, tolerability, pharmacokinetics, and immunogenicity of m102.4 in healthy adults. Methods: In this double-blind, placebo-controlled, single-centre, dose-escalation, phase 1 trial of m102.4, we randomly assigned healthy adults aged 18–50 years with a body-mass index of 18·0–35·0 kg/m 2 to one of five cohorts. A sentinel pair for each cohort was randomly assigned to either m102.4 or placebo. The remaining participants in each cohort were randomly assigned (5:1) to receive m102.4 or placebo. Cohorts 1–4 received a single intravenous infusion of m102.4 at doses of 1 mg/kg (cohort 1), 3 mg/kg (cohort 2), 10 mg/kg (cohort 3), and 20 mg/kg (cohort 4), and were monitored for 113 days. Cohort 5 received two infusions of 20 mg/kg 72 h apart and were monitored for 123 days. The primary outcomes were safety and tolerability. Secondary outcomes were pharmacokinetics and immunogenicity. Analyses were completed according to protocol. The study was registered on the Australian New Zealand Clinical Trials Registry, ACTRN12615000395538. Findings: Between March 27, 2015, and June 16, 2016, 40 (52%) of 77 healthy screened adults were enrolled in the study. Eight participants were assigned to each cohort (six received m102.4 and two received placebo). 86 treatment-emergent adverse events were reported, with similar rates between placebo and treatment groups. The most common treatment-related event was headache (12 [40%] of 30 participants in the combined m102.4 group, and three [30%] of ten participants in the pooled placebo group). No deaths or severe adverse events leading to study discontinuation occurred. Pharmacokinetics based on those receiving m102.4 (n=30) were linear, with a median half-life of 663·3 h (range 474·3–735·1) for cohort 1, 466·3 h (382·8–522·3) for cohort 2, 397·0 h (333·9–491·8) for cohort 3, and 466·7 h (351·0–889·6) for cohort 4. The elimination kinetics of those receiving repeated dosing (cohort 5) were similar to those of single-dose recipients (median elimination half-time 472·0 [385·6–592·0]). Anti-m102.4 antibodies were not detected at any time-point during the study. Interpretation: Single and repeated dosing of m102.4 were well tolerated and safe, displayed linear pharmacokinetics, and showed no evidence of an immunogenic response. This study will inform future dosing regimens for m102.4 to achieve prolonged exposure for systemic efficacy to prevent and treat henipavirus infections. Funding: Queensland Department of Health, the National Health and Medical Research Council, and the National Hendra Virus Research Program.